Investigating the Impact of Learning Interest on Student Achievement in Javanese Language Courses at State Senior High Schools - Rintra Julis Primastami; Nur Hanifah Insani (AL-ISHLAH: Jurnal Pendidikan, 2024)
Learning interest is a critical factor influencing students' academic achievement. This study examines the relationship between students' interest in learning and their learning outcomes in Javanese language lessons, emphasizing its role in preserving cultural heritage. A quantitative approach with a correlational research design was employed. The study was conducted at State Senior High School 2 Purbalingga, involving a population of 368 eleventh-grade students. Using simple random sampling, 192 students were selected. Data were collected through interviews, questionnaires, and documentation, and analyzed using simple regression and the product-moment correlation formula. The findings indicate a significant relationship between students' learning interest and their learning outcomes in Javanese language lessons, with a calculated r-value of 0.670 and a p-value 0.05 (0.000). These results demonstrate a moderately strong positive correlation, suggesting that higher interest in learning is associated with better academic performance. The results highlight the importance of fostering interest in learning to improve academic outcomes and support the integration of cultural values through education. Internal factors, such as motivation, and external factors, such as teaching methods, are crucial in enhancing student engagement. This study underscores the positive impact of learning interest on academic achievement in Javanese language lessons. The findings contribute to strategies aimed at improving educational outcomes while preserving cultural heritage, emphasizing the need for innovative teaching methods and stakeholder collaboration.